2014
DOI: 10.1371/journal.pone.0100123
|View full text |Cite|
|
Sign up to set email alerts
|

Development of Highly Sensitive and Specific mRNA Multiplex System (XCYR1) for Forensic Human Body Fluids and Tissues Identification

Abstract: The identification of human body fluids or tissues through mRNA-based profiling is very useful for forensic investigations. Previous studies have shown mRNA biomarkers are effective to identify the origin of biological samples. In this study, we selected 16 tissue specific biomarkers to evaluate their specificities and sensitivities for human body fluids and tissues identification, including porphobilinogen deaminase (PBGD), hemoglobin beta (HBB) and Glycophorin A (GLY) for circulatory blood, protamine 2 (PRM2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
20
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 47 publications
(100 reference statements)
7
20
0
3
Order By: Relevance
“…This is consistent with other studies where MMP7 and MMP11 appeared equally useful in the determination of menstrual secretion although MMP7 seems to be more sensitive; as higher signals were obtained when compared to MMP11 throughout menstrual days (Hass et al, 2009;Song et al, 2015;Lindenbergh et al, 2012;Xu et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with other studies where MMP7 and MMP11 appeared equally useful in the determination of menstrual secretion although MMP7 seems to be more sensitive; as higher signals were obtained when compared to MMP11 throughout menstrual days (Hass et al, 2009;Song et al, 2015;Lindenbergh et al, 2012;Xu et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…In 2003, using standard RT-PCR and gel electrophoresis, Juusola and Ballantyne reported that mRNAs specific for saliva and semen can be detected in stains as old as 10 weeks (15,57). The mRNAs have been used for identification of human body fluids or tissues, which is very useful for forensic investigations to identify the origin of biological samples (3,58). In 2005, Juusola and Ballantyne demonstrated the distinction of stains originating from different body fluids such as blood, semen, saliva and vaginal secretions (59).…”
Section: Extracellular Dna and Rnamentioning
confidence: 99%
“…В целом, как следует из разных публикаций по ра-боте с серийными разведениями, мультиплексный ПЦР на основе мРНК обладает высокой чувствительностью и может улавливать до 5-8 пг РНК, что соответствует количеству РНК в одной клетке [11,12].…”
Section: выделение нуклеиновых кислотunclassified
“…В последующие годы за счет открытия и внедре-ния новых маркеров появились новые версии панели «CellTyper», равно как и её аналоги [11], и настоящая, третья версия (CellTyper -v.3) включает в себя 19 мРНК-маркеров (см. табл.…”
Section: полимеразная цепная реакцияunclassified
See 1 more Smart Citation